New cases of human diphyllobothriosis in Patagonia, Argentine Novos casos de difilobotriosis humana na região da Patagônia, Argentina - Liliana Semenas; Ana Kreiter; Javier Urbanski (Universidade de São Paulo, 2001)
The purpose of the paper is to describe 4 new cases of human diphyllobothriosis in Patagonia, Argentine. Adult parasites recovered were submitted to morphological and histological analyses for taxonomic identification. The etiological agent found was always Diphyllobothrium latum and all the cases were autochthonous. These data combined with previous information make the number of autochthonous human cases of diphyllobothriosis registered in Argentina increase to 18. Foram descritos 4 novos casos de difilobotriosis humana na Patagônia, Argentina. Os parasitas adultos foram submetidos a análises morfológicas e histológicas para identificação taxonômica. O agente etiológico foi sempre Diphyllobothrium latum, e todos os casos de difilobotriosis foram autóctones. Esses novos registros se somam aos já previamente detectados, totalizando 18 casos humanos autóctones registrados na Argentina.